An Audience Interpretation of Professional Athlete Self-Presentation on Twitter - Katie Lebel; Karen Danylchuk (Journal of Applied Sports Management, 2014)
This study explored how sport consumers interpret athlete self-presentation on Twitter and distinguished the perceived importance of digital self-presentation on athlete image. A self-administered online survey based on Goffman’s (1959) theoretical framework of self-presentation was created to measure audience interest in the digital presentation strategies used by athletes. A definition and specific example were provided for 10 self-presentation strategies, after which participants were asked to rate their level of interest ( N = 377). The most salient strategy reported was that of the sport insider. Participants reported greatest interest in the discussion of athlete performance, athlete fitness, and an athlete’s sport expertise. The study suggests that fans may not be as interested in the personal details of an athlete’s life outside of sport as previously suggested. A disconnect between the self-presentation strategies being employed by athletes on Twitter and the strategies sport consumers report being most interested in was also identified.
Keywords: self-presentation; Twitter; professional athletes; digital marketing; audience interpretation